Stress process model : young adults on Instagram, perceived self-discrepancy and psychological distress - Ng, Jacobbina Jin Wen (2019)
There are ample grounds that tie social media use to negative mental health outcomes, including stress, loneliness, anxiety, and depression (see Berryman, Ferguson and Negy 2018; Hunt et al. 2018). Often, evidence indicates that factors such as addiction, cyberbullying, and exposure to traumatising content mediate the relationship between social media use and negative mental health consequences. Here, we draw on the stress process model to examine the relationship between real-ideal self-discrepancy and psychological distress (depression and anxiety) through the three moderators (social comparison, contingent self-esteem and self-efficacy). Results show that self-discrepancy is positively associated with both depression and anxiety. However, interestingly, the moderators are only significant between self-discrepancy and depression, but not anxiety.